Analisis beta karoten dari ekstrak jonjot buah labu kuning (Cucurbita moschata) - Dokri Gumolung (Jurnal Kimia Fullerene, 2017)
The purpose of this study was to identify compounds such as beta carotene, such as rubber extracts from various pumpkin strands extracts. Pumpkin plant as a minor food commodity, it is very rich in bioactive compounds that act as antioxidant very useful for human health. Strands in yellow fruit processing is often used as waste. This research was conducted by using laboratory analysis method through the following stages, determination and sampling, sample preparation, content analysis of beta carotene compound by spectrophotometer method at absorbance 445 nm. The results showed that strands of yellow pumpkin fruit contain beta carotene. In the extraction with Petroleum Ether (EPE), the beta-carotene content of EPE-strands 39.1 μg / g, ethanol extract (EET) of strands pumpkin flour, yielded 7.94 μg/g of beta carotene. The highest beta carotene content of the two extraction types EEP and EET are found in the extract with Petroleum Ether (EPE) because Petroleum Eter is a non-polar solvent which can dissolve less polar compounds that reside on cell walls such as terpenoids. Pumpkin fruit extract can be used as food fortification to increase the nutritional value.